Seeking gender-affirming medical care: A phenomenological inquiry on skillful coping with transgender and non-binary adults in the United States Midwest - Katie Heiden-Rootes; Dixie Meyer; Renata Sledge; Bryce K. Davis; Theresa Drallmeier; Whitney Linsenmeyer; Samantha Levine; Michelle R. Dalton (Qualitative Research in Medicine & Healthcare, 2023)
This study sought to understand how transgender and gender non-binary (TGNB) individuals skillfully cope with healthcare services and to explore how childhood experiences impact expectations, habits, and meaning-making when utilizing healthcare services. Using an interpretive phenomenological approach, we sampled 17, White TGNB adults in the United States, ages 19 to 57, using semi-structed interviews about childhood experiences with healthcare utilization and adult experiences seeking genderaffirming healthcare. Analysis identified one main theme—Anticipate the worst in healthcare and be pleasantly surprised—and three subthemes: i) contrast between positive childhood and negative adulthood experiences in medical care; ii) coping practices for the worst; and iii) finding your unicorn doctor and medical staff for pleasant experiences. Results indicate participants experienced a disruption and acquisition of new coping practices in healthcare settings and the cultivation of a radical imagination for a more liberated medical world for TGNB people. Implications for providers and medical offices for empowering TGNB adults are described.